Blood Pressure Variability in Acute Ischemic Stroke: The Role of Early Recanalization - Martins, AI (2018)
We performed a retrospective study with the aim of investigating the association between blood pressure (BP) variability in the first 24 h after ischemic stroke and functional outcome, regarding arterial recanalization status. A total of 674 patients diagnosed with acute stroke and treated with revascularization therapies were enrolled. Systolic and diastolic BP values of the first 24 h after stroke were collected and their variation quantified through standard deviation. Recanalization state was evaluated at 6 h and clinical outcome at 3 months was assessed by modified Rankin Scale. In multivariate analyses systolic BP variability in the first 24 h post-stroke showed an association with 3 months clinical outcome in the whole population and non-recanalyzed patients. In recanalyzed patients, BP variability did not show a significant association with functional outcome.